2023
DOI: 10.1002/ijgo.14637
|View full text |Cite
|
Sign up to set email alerts
|

Increased nuchal translucency with normal karyotype and genomic microarray analysis: A multicenter observational study

Abstract: Objective To define the residual risk of morbidity‐related outcome in fetuses with nuchal translucency (NT) of 3.5 mm or more after normal genetic testing and mid‐trimester anomaly scan. Methods A total of 114 fetuses with isolated NT of 3.5 mm or more, normal karyotype, and array‐based comparative genomic hybridization (array‐CGH) were included and divided in three groups: NT 3.5–4.5 mm, NT 4.5–6 mm, and NT greater than 6 mm. RASopathy testing and ultrasound follow up were performed in all fetuses. We evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
2
0
0
Order By: Relevance
“…This is in line with the results of Metzenbauer et al [33], who found that trisomies are associated with a higher NT and smaller placental volume between 11 and 14 weeks of gestation. Based on the literature, we can confirm that a low sHLA-G expression is commonly associated with implantation failure and miscarriage [10,34], as was also confirmed by our results, since an obvious correlation exists between increased nuchal translucency and fetal loss [35]. One can speculate that a lower sHLA-G level measured in the amniotic fluid may play a role in embryonic/fetal development.…”
Section: Discussionsupporting
confidence: 89%
“…This is in line with the results of Metzenbauer et al [33], who found that trisomies are associated with a higher NT and smaller placental volume between 11 and 14 weeks of gestation. Based on the literature, we can confirm that a low sHLA-G expression is commonly associated with implantation failure and miscarriage [10,34], as was also confirmed by our results, since an obvious correlation exists between increased nuchal translucency and fetal loss [35]. One can speculate that a lower sHLA-G level measured in the amniotic fluid may play a role in embryonic/fetal development.…”
Section: Discussionsupporting
confidence: 89%
“…This figure is comparable to the 81% reported in a previous study conducted in the Netherlands [18]. There are many recent studies showing that enlarged NT is associated with adverse pregnancy outcomes [19][20][21]. These findings highlight the importance of close surveillance of pregnancy with enlarged NT and anormal karyotype.…”
Section: Discussionsupporting
confidence: 82%